Sistem Pendukung Keputusan dalam Pemilihan Surat Kabar Online Terbaik dengan Metode WASPAS - Mesran; Ahmadfauzy; Aniyanti Tafonao; Mahesa Raihan Rifqi; Setiawansyah (Journal of Decision Support System Research, 2025)
The development of the internet makes it easier for us to get information, we don't have to buy newspapers or magazines to get information. We only use various social media to get information easily and quickly. This online newspaper provides many benefits for us in getting information, but in getting information online we need to be careful because there are also positive and negative impacts in this online newspaper. Sometimes they provide information that is not filtered first and are wrong in providing the information and the news is not clear so that there are often promblematics for many people in reading information on social media. So in solving the problems that occur in the selection of online newspapers, several criteria are needed including Reputation & Credibility, News Content, Journalism Quality, Platform Availability and Interactivity Level. So that in solving the above problems, the author needs a tool to solve the problem, namely SPK. SPK is a computerised tool in problem solving using real data in order to get or obtain clear and accurate information results. In this study the authors used the WASPAS method to find the final results accurately. So with that, the one who gets the highest rank in the selection of the best online newspaper is Kompas.com with a value of 1 and followed by Detikcom with an acquisition value of 0.76032.